Influencia del tráfico vehicular en la calidad del aire de la ciudad de Loja a través del biomonitoreo de Tillandsia usneoides - Cango González, María Belén (2023)
Emissions from vehicular traffic are directly related to the vehicle fleet, however, there are some considerations to be able to determine the impact that these are producing. Among the main compounds emitted by vehicular traffic are heavy metals, particulate matter 2,5; Sox; NOx; O3, among others. That is why there was a need to study the inference that vehicular traffic has on the air quality of Loja city, this through the use of Tillandsia usneoides, which is a bioaccumulator organism. Together with a study of sedimentable dust through passive collectors, and an Arduino sensor to record the behavior of particulate matter 2.5 (PM) in the urban area of the city. For this study, 12 sample points were selected, subdivided as follows: north (3), center (3), south (3) and control point (3). The sampling time for PM and settleable dust was estimated for two and a half months, while the biomonitoring consisted of taking 60 samples, five samples for the 12 sampling points. The results obtained showed that the air quality in Loja city is within the good range that goes from 0 to 50, nevertheless, when carrying out the laboratory analysis for sedimentable dust, in the northern zone, specifically in the point 11 corresponding to "Las Pitas" the concentrations exceed the maximum limit allowed by national regulations, this may be due to the fact that it is a heavy transport step and there is a large influx of vehicles because it is a commercial area. In the same way, when carrying out the analysis of lead, copper and cadmium in Tillandsia, it was observed that the absorbed concentrations are very low, therefore, it can be inferred that high concentrations of these are not generated at the sampling points. metals that come mainly from vehicular traffic. Keywords: biomonitoring, vehicular traffic, particulate matter, heavy metals, air pollution.